Structural Basis of GABAB Receptor Activation during Evolution - Hou, Guofei; Zhang, Shenglan; Shen, Cangsong; Ji, Suyu; Zou, Binqian; Xu, Chanjuan; Li, Liang; Shen, Dandan; Liang, Jiayin; Chen, Haidi; Rondard, Philippe; Deng, Cheng; et al. (Advanced science, 2025)
GABAB receptor is a Class C G protein-coupled receptor (GPCR) for γ-aminobutyric acid (GABA), the principal inhibitory neurotransmitter. It forms an obligatory heterodimer consisting of two subunits, GB1 and GB2. Whether the activation mechanism of the GABAB receptor is conserved during evolution remains unknown. Here, the cryogenic electron microscopy (cryo-EM) structures of the drosophila GABAB receptor in both antagonist-bound inactive state and GABA-bound active state in complex with Gi protein are reported. The drosophila GABAB receptor exhibits an asymmetric activation, mirroring its human homolog. However, a larger inactive interface prevents drosophila GABAB receptor constitutive activity. Four key residues, which are not conserved in drosophila GABAB receptor, are responsible for the activity of the positive allosteric modulator in its human homolog. Whereas the intracellular loop 2 of drosophila GB2 (dGB2) is less involved, the ordered C terminus of dGB2 and its corresponding region in its human homolog are required for G protein coupling. These evolutionary variations provide a complete understanding of the activation mechanism of the GABAB receptor and new insights for future development of allosteric modulators for medication and insecticides.GABAB receptor is a Class C G protein-coupled receptor (GPCR) for γ-aminobutyric acid (GABA), the principal inhibitory neurotransmitter. It forms an obligatory heterodimer consisting of two subunits, GB1 and GB2. Whether the activation mechanism of the GABAB receptor is conserved during evolution remains unknown. Here, the cryogenic electron microscopy (cryo-EM) structures of the drosophila GABAB receptor in both antagonist-bound inactive state and GABA-bound active state in complex with Gi protein are reported. The drosophila GABAB receptor exhibits an asymmetric activation, mirroring its human homolog. However, a larger inactive interface prevents drosophila GABAB receptor constitutive activity. Four key residues, which are not conserved in drosophila GABAB receptor, are responsible for the activity of the positive allosteric modulator in its human homolog. Whereas the intracellular loop 2 of drosophila GB2 (dGB2) is less involved, the ordered C terminus of dGB2 and its corresponding region in its human homolog are required for G protein coupling. These evolutionary variations provide a complete understanding of the activation mechanism of the GABAB receptor and new insights for future development of allosteric modulators for medication and insecticides.